Analisis Value Added Activity Berbasis Lean Hospital Pada Penyelesaian Klaim BPJS Rawat Inap RSIA Mutiara Bunda Padang - Ningdia, Adisti; Astiena, Adila Kasni; Syah, Nurafrainin (Jurnal Rekam Medis dan Informasi Kesehatan, 2025)
RSIA Mutiara Bunda is a type C hospital where 89-94% of its patients come from BPJS Health patients. The current condition of the hospital is developing Hospital Management Information System (SIMRS), but still using manual medical record files to complete evidence of inpatient BPJS claims. In preliminary research, it was found that 99% of medical record files did not comply with the 2x24 hour file return standard and the claim settlement deadline. A mix-method sequential exploratory was held, identifying activities that are value-added(VA), non value-added (NVA), and necessary non value-added (NNVA). The results of the study showed that the percentage of activity in completing claims for BPJS patient inpatient files at RSIA Mutiara Bunda consisted of VA of 1.47%, NNVA of 1.30%, and NVA of 97.23% (in the form of waiting time / idle).